The global death and disability burden associated with a high BMI in children and adolescents, 1990–2019 - Song, Ying; Zhou, Yuan; Feng, Xiaojin; Fu, Jieting; Liu, Yongping (Frontiers in Endocrinology, 2024)
Objective Exploring changing trends in the burden caused by overweight and obesity among children and adolescents from 1990 to 2019 at the global, regional, and national levels, based on data from the Global Burden of Disease study (GBD) 2019. Methods The annual number and rate of deaths and disability-adjusted life years (DALYs) associated with a high BMI among children and adolescents at global, regional, and national levels by age groups, sexes, and the sociodemographic index from 1990 to 2019 were collected from the GBD study 2019. Change percentage for number, and the estimated annual percentage changes (EAPCs) for rate were calculated to determine the temporal trends. Results From 1990 to 2019, global high BMI-related deaths decreased by 34% but DALYs increased by 48%. Death rates in females were higher than in males, although both showed decreasing trends. For the rate of DALYs, both sexes showed increasing trends, but since 1999, the rate in males has surpassed that in females. A high BMI had the greatest impact on children under 5 years of age, and the burden in other age groups continued to increase. Regionally, High-income Asia Pacific experienced the fastest decrease in death rate (EAPC=−9.57), and East Asia saw the fastest increase in the DALYs rate (EAPC= 3.47). Globally, as age increases, the proportion of disease burden attributed to a high BMI in females generally increases. Conclusions Our findings emphasize the urgent need to improve efforts to prevent children and adolescents becoming overweight and obese.